Female orchid bee Euglossa dilemma visits the perfume orchid Coryanthes panamensis in Florida - Pemberton, Robert W. (Lankesteriana: International Journal on Orchidology, 2024)
Male orchid bees gather fragrance chemicals from the surfaces of about 700 species of neotropical orchids and pollinate them in the process. The males display the collected chemicals during their courtship, and female orchid bees will mate only with males, displaying a species-specific blend of collected chemicals. Given this reality, the discovery of a female Euglossa dilemma dead in the bucket trap of a flower of the perfume orchid Coryanthes panamensis bearing the orchid’s pollinarium is extraordinary. There are no previous reports of female orchid bees visiting a perfume orchid and picking up pollinia of the orchids. Bearing a pollinarium indicates that this female bee made at least two visits to the flowers and that these visits were unlikely to be accidental. The flower in which the bee was found was on a cultivated plant grown in a residential garden in Coral Gables, Florida. Neither the orchid nor the orchid bee are native to Florida and occur in different areas of tropical America. Why this female orchid bee visited this orchid is considered, including the possibility that it may be a gynandromorph. Despite being a morphological female, the bee may have had neurological anomalies that caused it to exhibit a male-like attraction to this perfume orchid.